Still driven - Mobility patterns and gender roles in Portugal - Oliveira, Catarina Sales de (2014)
This article explores the relationship between gender and mobility based on the results of a PhD research about the mobility patterns in Portuguese metropolis. Mobility of human groups is one of the strongest trends of the last century with continuity to the present (Sheller and Urry, 2006). Although the empowerment of women in western societies, geographical mobility continues to be gender specific. If this situation is not new at international scene, in Portugal it raises interesting questions as the country has suffered recent and important social changes precisely in what concerns women roles. Using both an hypothetical deductive analytical model and combining quantitative with qualitative techniques in this research we were able to identify different mobility profiles according mainly to social identity in which gender performs a central role.